Binary evolution pulsating star - new evolutionary channel to produce RR Lyr-like pulsations - Karczmarek, P. (Advances in Astronomy and Space Physics, 2012)
In 2011 a promising candidate for an RR Lyrae star in an eclipsing binary system was found. Till that time not even one case of RR Lyrae star in a binary system has been known. The pulsator's mass is 0.26 Mꙩ which is not enough to burn helium in the core, as RR Lyrae stars do. The presence of a more massive companion is a clue that the mass transfer had to occur in the past. Therefore, Binary Evolution Pulsating (BEP) star, while having RR Lyr-like light curve, has completely unlike internal structure. The bulk of the star's mass was lost during the red giant phase due to mass transfer and the partially degenerated helium core with thin hydrogen burning shell was revealed. The BEP object has been captured inside the instability strip (IS) in the RR Lyrae area and thus it is confused with classical RR Lyrae pulsators. Therefore, the BEP star is the evidence of a new evolutionary channel to produce RR Lyr-like oscillations. In simulations made with StarTrack code we trace the evolution of a sample of binaries and examine properties of the system required for pulsation phase to occur. We suggest that the stars created via this new evolutionary channel can in part explain the existence of UV up-turn, low-mass C-O WD and He WD.